Grassroots Initiative for Religious Moderation: Overcoming Radicalism in Rural - Isnaini, Isnaini; Aniati, Ana (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2024)
This research analyzes grassroots initiatives for religious moderation in overcoming radicalism in rural areas. This research uses a qualitative case study approach. Data collection techniques use interview observation and documentation. Data analysis techniques use data reduction, data presentation, and conclusion. The research results show that grassroots initiatives through moderate religious education, strengthening local wisdom, cooperation and collaboration, and cultural and social approaches have successfully built collective awareness about the importance of religious moderation. These programs encourage active community involvement in maintaining harmony and preventing the spread of radical ideology. The success of this initiative was also marked by increased tolerance and solidarity among village residents, as well as a significant reduction in incidents of religious-based violence. This research confirms that a bottom-up approach to religious moderation has great potential in building community resilience against radicalism, especially in rural areas, vulnerable to external influences.